On Erosion Mechanisms of the Solid Surface under the Treatment with Submicrosecond Ion Beams; 7 International conference on modification of materials with particle beams and plasma flows - Bleykher (Bleicher) G. A. Galina Alekseevna (Modification of material properties, 2004)
Title from the title-page.